THU0741-HPR Placebo and nocebo effects induced by contextual factors. a survey on beliefs and attitudes of italian musculoskeletal physiotherapists. (15th June 2017) - Rossettini, G; Geri, T; Palese, A; Fiorio, M; Viceconti, A; Testa, M
Abstract : Background: Context effects are well known and were described as integral part of the clinical setting (1). The conscious use of contextual factors (CF) has been recently proposed as an effective modality capable to influence the physiotherapy outcome by facilitation of placebo responses. (2) To date, the knowledge about CF adoption in clinical practice of physical therapists is absent. Objectives: The aim of this study was to investigate frequency of use, beliefs and attitudes about contextual factors among Italian physical therapists specialized in manual therapy (OMTs) Methods: An invitation to participate in an online survey was sent to 906 OMTs through the database of the Master in Musculoskeletal Rehabilitation (MRDM) of University of Genova by SurveyMonkey Software®. These likely correspond to more than 85% of the whole OMTs population in Italy. A 17 items questionnaire and two clinical scenarios assessed behaviour, beliefs and attitudes of OMTs about CF adoption in clinical practice and data were analysed by descriptive statistic. Results: 906 OMTs were invited to participate in the survey and 558 responded (62%). The majority of OMTs uses CF in their practice frequently (52%). They believe that an actual effect of CF can occur in acute pain (57%), chronic pain (78%) and rheumatologic disorders (56%). OMTs consider the use of CF ethically acceptable when it exerts beneficial psychological effects and their effectiveness was shown during clinical experience (31%). They disagree on the adoption of CF when they are based on deception, undermine the trust between OMT and patients, create legal problems or produce side effects (17%). 38% of respondents do not communicate the use of CF to their patients and they adopt CF as addition to other physical therapy interventions with the aim of optimizing clinical responses (20%). Expectation and psychological mechanisms are believed to be the main aspects behind placebo and nocebo effects induced by CF (7%). Conclusions: The use of CF is quite common among Italian OMTs and they mostly had positive attitudes towards their use and effectiveness. References: Di Blasi Z, Harkness E, Ernst E, Georgiou A, Kleijnen J. Influence of context effects on health outcomes: a systematic review. Lancet. 2001 Mar 10;357(9258):757–62. Testa M, Rossettini G. Enhance placebo, avoid nocebo: How contextual factors affect physiotherapy outcomes. Man Ther. 2016;24:65–74. Disclosure of Interest: None declared